Generalised exponential consensus of the fractional-order nonlinear multi-agent systems via event-triggered control. Issue 6 (26th April 2019) - Shi, Min; Hu, Songlin; Yu, Yajuan
ABSTRACT: In this paper, the leader-following consensus problem of the fractional-order nonlinear multi-agent systems via event-triggered control is considered. An effective event-triggered controller is designed and then generalised exponential consensus of the controlled multi-agent systems is studied in the sense of Mittag-Leffler stability of fractional-order systems. The event-triggering function design is dependent on the parameter of the system structure and the minimum inter-event interval can be flexibly adjusted with different fractional-order α . With the event-triggered control scheme, the consensus condition is obtained and the convergence rate of the system is estimated. Numerical simulation indicates the effectiveness of the theoretical results.